Clinical Handover Standard for Midwifery Students: Improving Safety Attitudes in Maternity Services - Muchlis, Mumtihana; Indriasih, Merlita (Universitas Ahmad Dahlan, 2018)
Background: Midwifery students sometimes are not involved during the clinical handover in maternal health services, so they potentially get the negative impact on patient safety. This study was to assess the effect of the implementation of clinical handover standard for midwifery students as an effort to improve safety attitudes in maternity services. Method: A quasi-experimental with post test only design was conducted on 30 midwifery students at Amanda Maternity Services. Clinical handover standard with Situation, Background, Assessment and Recommendation (SBAR) Framework was used as a guideline. Results: Observation checklist was completed by Clinical Instructor (CI) while student and CI completed safety attitude questionnaire. A semi-structured interview was also conducted with midwifery student and clinical instructor. The result of this study showed that CI observation that 93.3% of students were competent in the application of clinical handover. Students’ safety attitudes also changed significantly after implementation of clinical handover standards (p= 0.0005). Conclusion: Majority of the students and clinical instructor stated that the application of clinical handover help students to reduce the confusion of the patients' problem to prevent errors in maternity care.